Role of survival post-progression in phase III trials of systemic chemotherapy in advanced non-small-cell lung cancer: a systematic review. - Katsuyuki Hotta; Katsuyuki Kiura; Yoshiro Fujiwara; Nagio Takigawa; Akiko Hisamoto; Eiki Ichihara; Masahiro Tabata; Mitsune Tanimoto (PLoS ONE)
Background In advanced non-small-cell lung cancer (NSCLC), with the increasing number of active compounds available in salvage settings, survival after progression to first-line chemotherapy seems to have improved. A literature survey was conducted to examine whether survival post-progression (SPP) has improved over the years and to what degree SPP correlates with overall survival (OS). Methods and findings Median progression-free survival (MPFS) time and median survival time (MST) were extracted in phase III trials of first-line chemotherapy for advanced NSCLC. SPP was pragmatically defined as the time interval of MST minus MPFS. The relationship between MPFS and MST was modeled in a linear function. We used the coefficient of determination (r(2)) to assess the correlation between them. Seventy trials with 145 chemotherapy arms were identified. Overall, median SPP was 4.7 months, and a steady improvement in SPP was observed over the 20 years (9.414-day increase per year; p<0.001) in parallel to the increase in MST (11.253-day increase per year; p<0.001); MPFS improved little (1.863-day increase per year). Overall, a stronger association was observed between MST and SPP (r(2) = 0.8917) than MST and MPFS time (r(2) = 0.2563), suggesting SPP and MPFS could account for 89% and 25% of the variation in MST, respectively. The association between MST and SPP became closer over the years (r(2) = 0.4428, 0.7242, and 0.9081 in 1988-1994, 1995-2001, and 2002-2007, respectively). Conclusions SPP has become more closely associated with OS, potentially because of intensive post-study treatments. Even in advanced NSCLC, a PFS advantage is unlikely to be associated with an OS advantage any longer due to this increasing impact of SPP on OS, and that the prolongation of SPP might limit the original role of OS for assessing true efficacy derived from early-line chemotherapy in future clinical trials.